The Syntax Analysis Of Adverb Of Manner Found In The Novel “Harry Potter” - wirawan, I Gede Nika (International Journal of Linguistics and Discourse Analytics, 2024)
This study entitled “The Syntax Analysis of Adverb of Manner Found in the Novel “Harry Potter”. The form of adverb of manner and its positions of adverb of manner found in the clause and sentence structure found in the novel entitled “The Lost Symbol” are analyzed. The theory proposed by Brown and Miller (1991) was used in this study and it was supported by other theories in analyzing the form and the position in adverb of manner found in the sentence structure. The study implemented qualitative method in library research. The data were taken from the novel entitled “Harry Potter” that was written by J.K Rowling. The The research suggests that there were one form of adverb of manner found in the novel entitled “Harry Potter”. The adverb of manner is filled in the sentence structure in the form of adverb of manner and prepositional phrase. Suffix –ly can be in the positive form of the adjective. The form of adverb of manner is in the prepositional phrase characterized by a preposition as the head of adverbial.